First dorsal metacarpal artery flap in soft tissue reconstruction of recurrent thumb squamous cell carcinoma - Pauline Yap; Arman Zaharil Mat Saad; Wan Azman Wan Sulaimana; Siti Fatimah Noor Mat Johar2; Nurul Syazana Mohamad Shah (ResearchGate, 2023)
Background. Subungual squamous cell carcinoma (SCC) of thumb is a rare disease. However, it is the most common malignancy affecting the nail bed. Early recognition is crucial and important for prompt diagnosis and effective treatment. Often this tumour needs to be treated surgically with wide local resection, which results in a defect in the thumb. If not handled appropriately, such defects render restriction in functionality of the involved thumb as well as a poor aesthetic outcome. In the worst-case scenario, it may result in a poor function of involved hand. Thus, reconstruction of the involved thumb is necessary. The main aim of reconstruction is to regain the hands’ function and preserved the thumbs’ sensation. Secondarily, to have an aesthetically pleasing hand. Our hands carry out delegate job and important duty for daily function. Especially, the thumb working together with the other fngers to carry out the hand function as one unit. Loss of thumb function affects the whole performance of the hand. Case descriptions. We report a case of recurrent subungual squamous cell carcinoma of thumb, which had wide local resection and subsequently underwent soft tissue coverage with an islanded frst dorsal metacarpal artery (FDMA) perforator fap. One month after surgery, the patient was able to regain a good functional outcome of the hand. In this report, we discussed the procedures that had been done. Conclusion. The patient regained full functional hand after reconstruction with preserved sensation over distal thumb. The aesthetic outcome is satisfactory. The FDMA perforator fap is a very pliable and robust fap for reconstruction of distal thumb defect.